¿En qué momento se jodió el arte? Entre el espectáculo y la invención en el arte actual - Ramírez, Juan (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2022)
“When did art get fucked? Between spectacle and invention in contemporary art”. The monograph offers a reading of Mario Vargas Llosa’s The Spectacle Civilization (2012), with the intention of bringing to light the aesthetic prejudices upon which his criticism of contemporary art is based. For this, we will rely on the thesis stated by the American philosopher and art theorist Larry Shiner, who holds in The Invention of the Art (2001), that the notion we have of art is born from a historical process that defines and determines it, especially from the historical conditions of the economy and society of Europe in the 18th and 19th centuries. With this, we pave the way for a serious debate about the current condition of art and culture. Although Vargas Llosa triggered reviews, columns, and round tables in universities and different virtual publications we pretend here an understanding of his view from which he opposes current artistic manifestations. To do this, we will first explain the novelistic and aesthetic theories of the Peruvian author, which will allow us to understand his cultural criticism and, in the second part, dismantle the aesthetic prejudices from which he operates. Our conclusion is that the vision of the Peruvian Nobel laureate of an autonomous and free art that defies time has the irony of having a historical beginning, so trying to explain these temporal boundaries that border it allows us to understand it better.

El trabajo realiza una lectura del libro La civilización del espectáculo (2012) de Mario Vargas Llosa, teniendo como intención sacar a la luz los prejuicios estéticos de los que parte su crítica al arte contemporáneo. Para esto nos apoyaremos en las tesis expuestas por el filósofo estadounidense y teórico del arte Larry Shiner, quien sostiene, en The Invention of the Art (2001), que la noción que tenemos de arte nace de un proceso histórico que lo define y determina, especialmente por las condiciones históricas de la economía y sociedad de la Europa de los siglos XVIII y XIX. Con esto, allanamos el terreno para un debate serio sobre la condición actual del arte y la cultura. Si bien Vargas Llosa recibió reseñas, columnas, mesas de diálogo en universidades y diferentes publicaciones virtuales, de las cuales hacemos recuento, pretendemos aquí una comprensión de su mirada, desde la que parte para oponerse a las manifestaciones artísticas actuales. Para ello, explicaremos primero las teorías novelísticas y estéticas del autor peruano, lo que nos permitirá entender su crítica cultural para, en un segundo momento, desmontar los prejuicios estéticos que operan detrás de él. Nuestra conclusión es que la visión del nobel peruano de un arte autónomo y libre, que desafía al tiempo, tiene la ironía de poseer un inicio histórico, por lo que tratar de explicar dichas fronteras temporales que la bordean nos permite comprenderla mejor.
Keywords: Art; Craft; Vargas Llosa; Larry Shiner; System of fine arts; Arte; Artesanía; Vargas Llosa; Larry Shiner; Sistema de bellas artes; https://purl.org/pe-repo/ocde/ford#6.03.01